Accessibility and the bus system from concepts to practice - Tyler, Nick, 1954- (Thomas Telford, 2002)
Presents the theory and practice of accessibility and how this integrates into the real world of transportation. This book details the process of designing an accessible bus system, from the underlying principles to the implementation, monitoring and evaluation. It is for those seeking to develop and implement accessibility policy in other areas.